PENGOLAHAN LINDI TPA DENGAN METODE KOAGULASI DAN OZONASI - Latin Hanum Lalasari; Enjarlis Enjarlis (Widyariset, 2009)
Landfilling of municipal waste is a major problem of the waste management system in Indonesia. The generated leachate must be appropriately treated before being discharged into the environment because it ivas toxic. The aim of this research was to compare the coagulation, ozonation, coagulation-ozonation, and ozonation- coagulation processes of landfill leachate at  TPA Bantar Gebang Bekasi, to classify the result of landfill leachate treatment, and to provide an efficient methodf or the treatment ofleachates, in order to reduce pollutants' content to concentration values lower than the corresponding limits. The variables selected in this research were types of coagulant, dosage of coagulant, and time duration of ozonation process. Parameters selected in this research were colour, taste,  pH, Chemical Oxygen Demand ( COD), Total of Suspended Solid ( TSS), Chloride ion (Cl) and ammonia ion( NH4+). The result of research have shown that the best optimum method of landfall leachate treatment was coagulation-ozonation combination process using FeC13 0.25% as a coagulant and a ozonator (0.25 g 03//h) for 75 minutes at pH of 9. The process succeed to degrade the value of COD, Cl, NII; were about 90,91%, 13,45% , 6,68%, respectively and category of B grade for treated leachate.